Role of the circulation on the anthropogenic CO2 inventory in the North-East Atlantic: A climatological analysis - Carracedo, L.; Pérez, Fiz F.; Gilcoto, Miguel; Velo, A.; Padín, X. A.; Rosón, Gabriel (Progress in Oceanography, 2018)
9 pages, 4 figures, 1 table Climatology-based storage rate of anthropogenic CO2 (Cant, referred to year 2000) in the North-East Atlantic (53 ± 9 kmol s−1, 0.020 ± 0.003 Pg-C yr−1) is described on annual mean terms. Cant advection (32 ± 14 kmol s−1) occurs mostly in the upper 1800 m and contributes to 60% of the Cant storage rate. The Azores and Portugal Currents act as ‘Cant streams’ importing 389 ± 90 kmol s−1, most of which recirculates southwards with the Canary Current (−214 ± 34 kmol s−1). The Azores Counter Current (−79 ± 36 kmol s−1) and the northward-flowing Mediterranean Water advective branch (−31 ± 12 kmol s−1) comprise secondary Cant export routes. By means of Cant transport decomposition, we find horizontal circulation to represent 11% of the Cant storage rate, while overturning circulation is the main driver (48% of the Cant storage rate). Within the domain of this study, overturning circulation is a key mechanism by which Cant in the upper layer (0–500 dbar) is drawdown (74 ± 14 kmol s−1) to intermediate levels (500–2000 dbar), and entrained (37 ± 7 kmol s−1) into the Mediterranean Outflow Water to form Mediterranean Water. This newly formed water mass partly exports Cant to the North Atlantic at a rate of −39 ± 9 kmol s−1 and partly contributes to the Cant storage in the North-East Atlantic (with up to 0.015 ± 0.006 Pg-C yr−1). Closing the Cant budget, 40% of the Cant storage in the North-East Atlantic is attributable to anthropogenic CO2 uptake from the atmosphere (21 ± 10 kmol s−1). This work was funded by the Spanish National Research Council (CSIC), through the EU H2020 project AtlantOS (“Optimizing and Enhancing the Integrated Atlantic Ocean Observing Systems Research”, RIA), financed by the European Commission’s H2020 Framework Programme under grant agreement no. 633211. The first author is being funded by the University of Vigo, through the Galician I2C Plan for postdoctoral research. F.F. Pérez and G. Rosón were supported by the Spanish Ministry of Economy through the CATARINA ...